Relationship Between Jumping Ability, Agility and Sprint Performance of Elite Young Basketball Players: A Field-Test Approach - Abbas Asadi (Universidade Federal de Santa Catarina, 2016)
The purpose of this study was to determine the relationships between sprint, agility and jump performance of elite young basketball players. Sixteen elite national level young male basketball players participated in this study. The jumping ability of each player was determined using countermovement jump (CMJ), and broad long jump (BLJ). The agility T test (TT) and Illinois agility test (IAT) were assessed to determine the agility, and 20-m sprint time was also measured to determine sprint performance. The results of Pearson Product Moment Correlation analysis indicated moderate correlation between training age and IAT (r = -0.57; p = 0.021). Strong correlations were found between CMJ and BLJ (r = 0.71; p = 0.002), and between TT and IAT (r = 0.70; p = 0.002). Similarly, 20-m sprint time was strong correlated with CMJ (r = -0.61; p = 0.011), BLJ (r = -0.76; p = 0.001), TT (r = 0.77; p = 0.001), and IAT (r = 0.68; p = 0.003). In addition, CMJ was strongly correlated with TT (r = -0.60; p = 0.013), and IAT (r = -0.64; p = 0.007), and also strong correlation between BLJ with TT (r = -0.85; p = 0.001) and IAT (r = -0.76; p = 0.001). The findings of the present study indicated significant correlation between sprint and agility, jumping ability and sprint performance and between jumping ability and agility performance in basketball players. Therefore, the results suggest that sprint, agility and jumping ability share common physiological and biomechanical determinants.